ANALISIS PARIWISATA PRO-MISKIN: SUATU STUDI DI KABUPATEN/KOTA PROVINSI MALUKU UTARA - Elia Radianto; Gatot Sasongko; Ann Zusan de Bell; Sarlotha Yulliana Purimahua (LPSDI Bina Patria, 2023)
This study aims to analyze the influence of Tourism Participation Index (TPI), Social Development Indicator (SDI), Infrastructure Development Indicator (IDI), Human Resources Indicator (HRI) on the number of poor (JPM) in districts/cities of North Maluku Province using dynamic panel data during the period of 2012-2019. The data was analyzed using Feasible Generalized Least Square VI. The results show that the HRI is not significant, while the TPI and SDI have a significant and negative effect. In contrast, the IDI is significant and positive. Further, in the long run the TPI, SDI and IDI have a positive effect on the JPM. These results indicate that the tourism development in the districts/cities of North Maluku Province did not favor the poor. Therefore, Pro-Poor Tourism policy is needed and can be done through the involvement of the poor in the tourism development process, so that the development can provide space for the poor to get business opportunities